Pengaruh Environmental, Social, and Governance (ESG Performance) terhadap Manajemen Laba dengan Kepemilikan Manajerial dan Managerial Overconfidence sebagai Variabel Moderasi - Wulandari, Miranti; Sebrina, Nurzi (Jurnal Eksplorasi Akuntansi, 2025)
This study investigates the impact of ESG performance on earnings management, with managerial ownership and managerial overconfidence as moderating variables. Earnings management in this research is measured by discretionary accruals as a proxy. ESG performance is measured based on scores from Refinitiv Eikon. Managerial ownership is measured by the ratio of shares owned by managers to the total shares. Meanwhile, managerial overconfidence is measured by the comparison of the debt equity ratio (DER) to the industry median. The population for this study consists of all companies listed on the IDX in Indonesia from 2019 to 2023, selected using purposive sampling techniques, resulting in a total sample of 205 companies over 5 years of research. The results indicate that ESG performance does not have a significant effect on earnings management. However, managerial ownership weakens this relationship, while managerial overconfidence does not show a moderating effect.